PENGARUH BIAYA PRODUKSI TERHADAP PENDAPATAN PETANI MANDIRI KELAPA SAWIT DI KECAMATAN SEGAH - Abdul Hakim (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2018)
The purpose of this study was to analyze the income of independent oil palm farmers in the Segahdistrict. The analytical tool used are multiple linear regression equations, correlation coefficients, t test and calculated f test Based on the results of the analysis, it was found that the multiple linear regression equation influences the cost of seedlings, fertilizer costs and financing the eradication of weeds against the income of independent oil palm farmers in Segah district is Y = - 1,469 + 0,639 X1 + 4,150 x3 . To measure the degree of the correlation between seed costs, fertilizer costs and financing of weed eradication of the income of independent oil palm farmers in Segah district, the researcher used a multiple correlation coefficient (R) = 0.993 which means that the variable costs of seeds, fertilizer costs and weed eradication costs affect the income of farmers independent of oil palm in Segah District, the coefficient of determination R = 0.987 which showed that the income of independent farmers of oil palm in Segah district is influenced by seed costs, fertilizer costs, and weed eradication costs while the remaining 1.13% (1 - 0.987) is a factor which is not examined. Based on testing using f test where f arithmetic is 0.040 <0.10 and t count value is 2.617> 1.943, it can be concluded that the proposed hypothesis is accepted.